2021
DOI: 10.1007/s00256-020-03702-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of femoral component rotation after total knee arthroplasty in Kanekasu radiographs, axial CT slices and 3D reconstructed images

Abstract: Objective To compare the posterior condylar angle measured with Kanekasu radiograph and 2D-CT with the gold standard 3D-CT following primary total knee arthroplasty (TKA). Methods Eighty-two knees with pain following TKA were included in this retrospective study. Two independent raters measured the anatomical and surgical posterior condylar angles twice on each Kanekasu radiograph and 2D-CT. These measurements were compared against the 3D-CT measurement. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…If the reference on lateral condyle is unique on the apex of bony prominence, there are two possible references for the medial condyle: The apex of the medial prominence defines the anatomical TEA (A TEA); and the surgical TEA (S TEA) connects the lateral condyle and the medial sulcus on the femur. The chose A TEA, which was made according to Robertson et al conclusions, that is, the measurements using the A TEA transepicondylar axis are easier to replicate compared to the S TEA axis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the reference on lateral condyle is unique on the apex of bony prominence, there are two possible references for the medial condyle: The apex of the medial prominence defines the anatomical TEA (A TEA); and the surgical TEA (S TEA) connects the lateral condyle and the medial sulcus on the femur. The chose A TEA, which was made according to Robertson et al conclusions, that is, the measurements using the A TEA transepicondylar axis are easier to replicate compared to the S TEA axis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the results reported by Lei et al [ 10 ], who positioned and measured the deviation of the Whiteside line and the PCL positioned femoral prosthesis rotational alignment from sTEA in a reconstructed 3D CT model of the femur, with intra- and inter-observer ICC > 0.9, with good reproducibility. The results of the study conducted by Robertson et al [ 22 ] also indicated that compared to 2D CT, the accuracy and repeatability of locating reference axes were higher in 3D CT models. However, many studies [ 10 , 23 ] have performed CT scans of the entire femur to locate the mechanical axis of the femur in the 3D model, which can increase the exposure time to radiation and additional financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…But their included were all normal femora, and the included femora in this study were all KL grade II and above, so this study was closer to clinical reality, and the conclusions were more reliable. However, many studies that consider performing routine external rotation 3° osteotomy on patients do not take into account the anatomical variation of the distal femur [ 22 , 32 ], the asymmetric wear, varus deformity, etc., which can make PCA individualized [ 33 ], and routine external rotation 3° osteotomy is not accurate. In a cadaveric study, Mantass et al [ 34 ] reported that the sTEA relative to PCL external rotation angle ranged from − 1° to 7°, with a mean external rotation of 5°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation